104th Fresno County Bar Association Annual Bar Banquet-TorNino's - Watkins, Howard::::::::: (1986)
Out-going Fresno County Bar Association Board Member Anthony Capozzi receiving a plaque from Judy Soley; Herbert Levy, Howard Watkins, William J. Smith, Howard Zidenberg and Mary Louise Frampton at head table